Evaluation on the technical efficiency of Laak bamboo (Bambusa sp.2) culm production in Tagum City - Bilbao, Crishyl Ann P.
Bamboo has been ecologically, socially and commercially important plant in the Philippines and in other Asian countries. In the Philippines, one of the main industries that uses bamboo culms is the banana industry in Davao Region ( Virtucio and Roxas, 2004) Bamboo culms are used as propping to support banana plants from falling over during fruiting season. As of 2010, Davao region remained as the top banana producer in the country. The region utilizes a total of 0.45 million ha and since 2001-2010, the area covered by banana plantations increased with an annual average growth rate of 5%. With this, as the primary material for propping, it appears that Laak bamboo has economic advantage. Hence, this study would like to help the Laak bamboo producers to achieve optimal production by analyzing technical efficiency using Data Envelopment Analysis. Aside from determining the efficiency of Laak bamboo culm production in Tagum City, industry analysis was also performed. Laak bamboo culm production in Tagum City was found to be demand dependent specifically for the use of the banana industry. To achieve efficiency, bamboo producers of farms having inefficient level of production are advised to reduce their farm areas and the utilization of labor.